2012
DOI: 10.1097/scs.0b013e318240feed
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Study of the Inspiratory Upper Airway and Clinical Severity of Obstructive Sleep Apnea

Abstract: The apnea-hypopnea index (AHI) is a widely accepted measure for the severity of obstructive sleep apnea (OSA). Current methods to determine AHI fail to provide anatomic information for treatment decisions. In this report, we studied three-dimensional models of upper airways acquired by computed tomographic scanning with geometric measurements and computational fluid dynamics (CFD) analysis and evaluated the correlations with AHI.Participants had CT scans of their upper airways after standard polysomnography st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Several studies have reported the use of CFD to simulate the process of airway obstruction in OSA (21,28,30,33,34). Most studies have exclusively used a fixed airflow volume and/or velocity for CFD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the use of CFD to simulate the process of airway obstruction in OSA (21,28,30,33,34). Most studies have exclusively used a fixed airflow volume and/or velocity for CFD.…”
Section: Introductionmentioning
confidence: 99%
“…1). Similarly, Yu et al [30] predicted sharp pressure drops in the flow-limiting regions that were consistent with the apnea-hypopnea index (AHI). Large eddy simulations (LESs) of laryngeal flows included Lin et al [32] who observed significant effect of turbulent laryngeal jet on tracheal wall shear stress, Xi et al [33] who emphasized the importance of accurate glottis geometry in predicting airflows in the conducting airways, and Mihaescu et al [25] who demonstrated the superiority of large eddy simulation over Reynolds-averaged Navier-Stokes (RANS) methods using an image-based airway geometry representing severe OSA.…”
Section: Introductionmentioning
confidence: 58%
“…17,18 The effective and reliable prediction of a difficult intubation requires a combination of several parameters, including age, BMI, Mallampati score, head and neck movement, thyromental and sternomental distances, dentition status, and inter-incisal distance. 19 In the current study, parameters among these that are considered practical, easily repeatable, and non-invasive were used.…”
Section: Discussionmentioning
confidence: 99%